Effect of Educational Intervention on Communication Skills and Self-Efficacy of Primary Healthcare Workers (Behvarz) - Mansooreh Basiri; Mahmood Karimy; Hossein Shahnazi (Hamadan University of Medical Sciences, 2019)
Aims: Effective communication between primary healthcare workers and people is a critical skill for providing appropriate healthcare. The purpose of this study was to evaluate the impact of educational intervention on communication skills and self-efficacy of primary healthcare workers (Behvarz). Materials and Methods: This quasi-experimental study carried out between 104 people, who were the primary healthcare workers of health centers in Saveh and Zarandieh city in 2018. The primary healthcare workers of Saveh (60 people) were assigned to the test group and the primary healthcare workers of Zarandieh (44 people) were assigned to the control group. The test group received four 90 minute sessions training course on self-efficacy, and communication skills. Data were collected before the educational intervention and 2 months after the educational intervention by a questionnaire including demographic variables, self-efficacy, and a checklist of communication skills. Data were analyzed using SPSS 19 software through Chi-square test, paired sample t-test, and independent sample t-test. Findings: Based on the results, there was no significant difference between the mean scores of the self-efficacy and communication skills in the test and control groups before the educational intervention (p>0.05). After the educational intervention, a significant difference was observed in the all areas of communication skills (starting the session and creating a relationship, data collection, paying attention to people's point of view who referred to the health center and providing information, mutual agreement and ending the session) and self-efficacy (p<0.001). Also, the mean scores of self-efficacy and communication skills increased in the test group after the educational intervention (p<0.001). Conclusion: Educational intervention is effective on the improvement of communication skills and self-efficacy of primary healthcare workers.